Determinants of Non-Compliance in Consuming Blood Supplement Tablets among Young Women at SMA Negeri 1 Kayuagung in 2024 (HEALTH CARE: JURNAL KESEHATAN, 2025)
ABSTRACTAdolescence is a transition period from childhood to adulthood.  One of the problems faced by Indonesian teenagers is micronutrient nutrition. Nationally, the prevalence of adolescent anemia is still considered quite high. The program for providing blood supplement tablets (TTD) is experiencing problems with its intended target, namely young women. There is non-compliance in consuming the TTD. Hemoglobin examination on 177 class This study aims to determine the relationship between knowledge, attitudes, parental support, teacher support, health worker support, peer support, and access to information with non-compliance with consuming blood supplement tablets among young women at SMA Negeri 1 Kayuagung. Carried out in April-May 2024. This research is quantitative with a cross-sectional design, the population of this study is all 175 young women in class X at SMA Negeri 1 Kayuagung in 2024. Data collection and retrieval uses a questionnaire. The results of the statistical test analysis used the Chi-Square statistical test and logistic regression where the results showed that there was a significant relationship (p value < 0.05) for the attitude variable (0.001) with non-compliance with consuming blood supplement tablets. There is no relationship between the variables knowledge (1.000), parental support (0.500), teacher support (0.179), health worker support (1.000), peer support (1.000), and access to information (0.270) with non-compliance with consuming blood supplement tablets. It is recommended that the SMA Negeri 1 Kayuagung School, it is hoped, will increase the knowledge of female students about the importance of consuming blood supplement tablets (TTD). Keywords: Non-compliance, Blood Increasing Tablets, Teenagers